Raw Ground Penetrating Radar Data on North American Glaciers ... - Shad R O'Neel; Daniel McGrath; Gabriel J. Wolken; Erin N Whorton; S.G. Candela; Louis Sass; Christopher J. Mcneil; Emily H Baker; Erich H Peitzsch; Daniel B Fagre; Adam M Clark; Caitlyn E Florentine; et al. (U.S. Geological Survey, 2017)
U.S. Geological Survey researchers conducted time-series ground-penetrating radar (GPR) surveys with a Sensors and Software 500-MHz Pulse Ekko Pro system. This data release contains ground-based (ski and snowmobile) as well as airborne common-offset profiles. All profiles are linked to coincident GPS observations. Additionally, common-midpoint data was collected at specific glacier locations. Coincident in-situ data may provide calibration information, and may be composed of any of the following: snow pits and/or snow-pit/snow-core combinations, probe profiles, and ablation stake data. This supplemental information provides estimates of snow properties which may be used to calibrate radar velocity. ...